Analyzing the Content of Aqliyyah-Nafsiyyah Categories in Islamic Education at the Secondary Level - Husnul Rita Binti Aris; Saedah Binti Siraj; Zaharah Hussin (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
Islamic education in secondary schools has traditionally relied on Bloom's taxonomy for teaching and learning. However, there is currently no taxonomy based on the views of Islamic scholars for Islamic education. A new taxonomy called the Aqliyyah-Nafsiyyah taxonomy has been developed to address this gap. This taxonomy is based on the theories of three central figures: Ibn Sina, Al-Ghazali, and Al-Attas. The taxonomy was developed through a mixed-method quantitative and qualitative content analysis of the three main books of the three figures. The result of the qualitative content analysis identified five main categories and 22 sub-categories for developing the Aqliyyah-Nafsiyyah taxonomy of learning Islamic education at the secondary level. The contribution of the research lies in the unique perspectives of Ibn Sina, Al-Ghazali, and Syed Muhammad Naquib al-Attas on understanding human nature and education in the Islamic tradition. Their works have developed a taxonomy that can help navigate the complexities of human nature and education within an Islamic framework while addressing contemporary challenges to spiritual fulfilment.